High aortic pulse-wave velocity may be responsible for elevated red blood cell distribution width in overweight and obese people: a community-based, cross-sectional study - Altiparmak, Ibrahim Halil (Cardiovasc J Afr, 2016)
BACKGROUND: Obesity and overweight are risk factors for atherosclerosis. Red blood cell distribution width (RDW) is associated with subclinical cardiac diseases. The aim of this study was to investigate the association between RDW and aortic stiffness in overweight or obese subjects. METHODS: A total of 101 overweight or obese subjects without overt cardiovascular disorders, and 48 healthy controls were enrolled. RDW, aortic pulse-wave velocity (PWV) and augmentation index 75 (Aix75) were evaluated. The case subjects were divided into two sub-groups according to PWV values; ≥ 10 m/s in group I, and < 10 m/s in group II. Bivariate correlation and multiple regression analyses (stepwise) were performed. RESULTS: RDW and PWV were considerably increased in the case groups compared with the controls. RDW was significantly increased in group I compared with group II and the controls [median 12.0 m/s, interquartile range (IQR): 10.5–17.5; median 11.7 m/s, IQR: 10.2–14.2, and median 11.4 m/s, IQR: 9.6–15.5, p < 0.05, respectively]. Resting heart rate and age were higher in group I than group II (81 ± 11 vs 74 ± 12 beats/min and 41 ± 120 vs 36 ± 9 years, respectively, p < 0.05). Regression analyses revealed that while log-RDW, age and resting heart rate were independent predictors for aortic PWV, log-RDW was the most important predictor in the final model. CONCLUSIONS: RDW, resting heart rate and age independently predicted arterial stiffness, and RDW may be useful to provide an early recognition of subclinical atherosclerosis in overweight and obese individuals.